2018
DOI: 10.1038/s41593-018-0233-y
|View full text |Cite
|
Sign up to set email alerts
|

Neural implementation of Bayesian inference in a sensorimotor behavior

Abstract: Actions are guided by a Bayesian-like interaction between priors based on experience and current sensory evidence. Here we unveil a complete neural implementation of Bayesian-like behavior, including adaptation of a prior. We recorded the spiking of single neurons in the smooth eye-movement region of the frontal eye fields (FEF), a region that is causally involved in smooth-pursuit eye movements. Monkeys tracked moving targets in contexts that set different priors for target speed. Before the onset of target m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
123
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(138 citation statements)
references
References 51 publications
15
123
0
Order By: Relevance
“…Others have shown that task-related firing rates of single neurons before the presentation of sensory information may be modulated by prior expectations [83][84][85] , and firing rates after the presentation of sensory information may reflect Bayesian estimate of behaviorally-relevant variables 30,[86][87][88] . There have also been attempts to apply reliability-weighted linear updating schemescommonly used in cue combination studies [89][90][91] -to explain how single-neuron firing rates might combine sensory evidence with prior expectations 92,93 . However, the fact that single neurons encode various components of Bayesian models has not led to an overarching framework for understanding how networks of neurons perform Bayesian computations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have shown that task-related firing rates of single neurons before the presentation of sensory information may be modulated by prior expectations [83][84][85] , and firing rates after the presentation of sensory information may reflect Bayesian estimate of behaviorally-relevant variables 30,[86][87][88] . There have also been attempts to apply reliability-weighted linear updating schemescommonly used in cue combination studies [89][90][91] -to explain how single-neuron firing rates might combine sensory evidence with prior expectations 92,93 . However, the fact that single neurons encode various components of Bayesian models has not led to an overarching framework for understanding how networks of neurons perform Bayesian computations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, natural statistics are thought to shape tuning properties and/or spontaneous activity of neurons through adjustments of synaptic connections in early sensory areas [6][7][8][9][10] . Single-unit responses in higher-level cortices also encode recent sensory events 11 , motor responses [12][13][14] , and reward probabilities [15][16][17][18] . However, an understanding of how experience-dependent neural representations enable Bayesian computations is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…More recently an effort has been made to provide a more general theoretical framework, which is based on Bayesian inference and the reliability-based cue combination. Although the mapping of this theoretical framework onto neuronal functions remains to be elucidated, it has the clear advantage of generality, as for instance, it would encompass all forms of smooth pursuit behavior, including prediction-based and visually-guided tracking [42][43][44][45].…”
Section: Anticipatory Smooth Pursuit Eye Movements (Aspem)mentioning
confidence: 99%
“…Preparation is an important component of voluntary movement. Throughout the motor system, many neurons show modulation of firing rate that occurs during movement preparation that is linked to parameters of the ensuing movement (Dorris et al, 1997; Glimcher and Sparks, 1992; Hanes and Schall, 1996; Munoz and Wurtz, 1995; Tanaka and Fukushima, 1998; Tanji and Evarts, 1976; Weinrich and Wise, 1982; Wurtz and Goldberg, 1972; Churchland et al, 2006a, 2006b; Darlington et al, 2018; Hanes and Schall, 1996; Mahaffy and Krauzlis, 2011; Messier and Kalaska, 2000). Importantly, many neurons that seem to be tied to movement still have preparatory activity, even though there is neither movement nor muscle activity during preparation.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the same cells that discharge in relation to the initiation of pursuit also show an impressive ramp increase in firing rate during fixation, at a time when there is neither visual motion nor smooth eye movement (Mahaffy and Krauzlis, 2011; Tanaka and Fukushima, 1998). The preparatory activity grows over the hundreds of milliseconds preceding visual motion and the onset of pursuit, and its amplitude encodes expectation of upcoming target speed and combines with visual-motion input in a reliability-weighted manner to determine pursuit-related responses (Darlington et al, 2018).…”
Section: Introductionmentioning
confidence: 99%